Development of PET Radioligands Targeting COX-2 for Colorectal Cancer Staging, a Review of in vitro and Preclinical Imaging Studies - Dagallier, Caroline; Avry, François; Touchefeu, Yann; Buron, Frédéric; Routier, Sylvain; Chérel, Michel; Arlicot, Nicolas (Frontiers in Medicine, 2021)
Colorectal cancer (CRC) is the second most common cause of cancer death, making early diagnosis a major public health challenge. The role of inflammation in tumorigenesis has been extensively explored, and among the identified markers of inflammation, cyclooxygenase-2 (COX-2) expression seems to be linked to lesions with a poor prognosis. Until now, COX-2 expression could only be accessed by invasive methods, mainly by biopsy. Imaging techniques such as functional Positron Emission Tomography (PET) could give access to in vivo COX-2 expression. This could make the staging of the disease more accurate and would be of particular interest in the exploration of the first metastatic stages. In this paper, we review recent progress in the development of COX-2 specific PET tracers by comparing the radioligands’ characteristics and highlighting the obstacles that remain to be overcome in order to achieve the clinical development of such a radiotracer, and its evaluation in the management of CRC.